A Descriptive Study of Occupational Health Services in Self-employed Enterprises (Nanoscale Enterprises), Shiraz, Iran - Mehdi Jahangiri; Akbar Rostamabadi; Parvaneh Yekzamani; Bahare Mahmood Abadi; Fariborz Behbood; Seyyedeh Fatemeh Ahmadi; Zahra Momeni (Elsevier, 2016)
Background: This study was conducted with aim of providing an overview of the current status of occupational health services and identifying the most common harmful agents at workplaces of Iranian self-employed enterprises (Nano-Scale Enterprises). Methods: A cross-sectional study was performed among a random sample including 1,758 employees engaging in self-employed enterprises with 5 and less employees. Results: Coverage of occupational health surveillance was very poor, annual health examinations were been conducted only for 64 (3.64%) of males and 31 (1.76%) of females, and occupational health trainings were not included of the services at all. Personal Protective Equipment were available in 462 (26.3%) of the enterprises. only in 0.4% of the enterprises working processes were been equipped by a local exhaust ventilation system. Difficult postures were the most common (81.5%) adverse working conditions. Conclusion: This study revealed a poor level of the implementation of occupational health services in Iranian self-employed enterprises. Based on the findings, providing basic training on the occupational health, more enforcing in conduction of health examinations and providing PPE, and taking appropriate strategies aimed at eliminating or minimizing work environment harmful agents are the major factor that should be considered to improve the level of occupational health services among the studied enterprises.